MODEL KOMUNIKASI PERUBAHAN SOSIAL DALAM MENDORONG ADOPSI PERILAKU ZERO WASTE PADA MASYARAKAT URBAN DI KOTA SERANG - Malik, Abdul (Jurnal Silva Samalas, 2025)
Rapid urbanization has accelerated waste generation in medium-sized Indonesian cities, including Serang City, Banten Province, which produced approximately 584.83 tonnes of waste per day in 2023, while the reduction rate reached only 0.77 percent. This gap indicates that a purely infrastructural approach to waste management is insufficient without engaging citizens in behavioural change. This study aims to construct a conceptual model of social change communication that can encourage the adoption of zero waste behaviour among the urban population of Serang City. A qualitative descriptive method through library research (desk study) was applied, synthesising secondary data from scientific journals, government reports, and regional regulations published between 2019 and 2024. Data were analysed using an interactive qualitative content-analysis technique consisting of data reduction, data display, and conclusion drawing, informed by diffusion of innovation theory, social marketing, and community-based social marketing. The results indicate that behavioural adoption in Serang is shaped by five interrelated communication stages: awareness building, participatory persuasion and education, social engagement through local change agents, institutionalisation through digital incentive systems, and evaluation with public feedback. The proposed model emphasises the integration of local socio-cultural values, such as mutual cooperation (gotong royong), with digital waste-bank incentives to sustain behavioural change. This model offers a contextual communication framework that local governments and environmental agencies can adapt to strengthen community participation in sustainable urban waste management.